Early Alterations in De Novo Parkinson’s Disease Revealed by Diffusion Tensor Imaging: Preliminary Study - Francesca Di Giuliano; Noemi Pucci; Maria Lina Serio; Eliseo Picchi; Silvia Minosse; Valentina Ferrazzoli; Valerio Da Ros; Tommaso Schirinzi; Matteo Conti; Roberta Bovenzi; Davide Mascioli; Francesco Garaci (Diagnostics)
Background/Objectives: Parkinson’s disease (PD) is characterized by progressive neurodegeneration affecting both motor and non-motor functions. Identifying early alterations in PD patients before the onset of dopaminergic therapy is crucial for understanding disease progression and developing targeted interventions. This study aimed to investigate early changes in the putamen and thalamus in de novo PD patients using diffusion tensor imaging (DTI) compared to healthy controls. Methods: Thirty-one de novo PD patients and thirty-three healthy controls underwent DTI scanning. Tract-based spatial statistics were used to compare fractional anisotropy (FA) values between groups. Results: De novo PD patients exhibited significantly lower FA values in the right thalamus compared to controls, suggesting alterations in neuronal integrity or fiber degeneration in the early stages of the disease. However, no significant differences were demonstrated for FA values in the putamen between groups. Conclusions: We demonstrated that the FA value in the right thalamus was lower in PD compared with healthy controls. These findings highlight the potential of DTI as a non-invasive tool for detecting early neural changes in PD patients. Further studies would be helpful to assess the clinical utility of serial FA measurements of the subcortical gray matter in objective quantification of disease progression and monitoring of the therapeutic response.